Effect of technology on environmental pollution: empirical evidence for 122 countries grouped according to their income level - Ruiz, Yomara (2021)
This research aims to evaluate the effect of technology on environmental pollution. Econometric techniques of panel data are used through quantile regressions of Canay, Powell and Chernozhukov, Fernández-Val & Melly, this methodology allows to capture the heterogeneous distribution of the slope. The data were obtained from the World Bank's WDI (2020) for 122 countries classified according to their income level in the period 1996 - 2018. The results focus on the fulfillment of the Kuznets curve at the global level, PIA and PIMB, where a heterogeneity distribution was evidenced in the quantiles. Likewise, exports and income from natural resources showed a positive effect on environmental pollution along the distribution by quantiles. The contribution of the research is to contribute to the existing empirical evidence, obtaining new results through a methodology that has not been estimated in previous studies. That is why governments must implement rigid environmental laws that prevent the increase in environmental pollution, in such a way that companies invest in green technologies. Likewise, generate restrictive policies for the establishment of foreign companies that pollute the environment through their productive activities.